Moderasi Beragama di Era Digital: Tantangan Dakwah di Tengah Polarisasi Media Sosial pada Mahasiswa Semester 1 IAINU Tuban - Muhammad Habib Ainur Rosyid; Dina Amalia; Fitriani Luthfiyah Q.A; Dwi Aminatus Sa’adah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of digital information technology has fundamentally transformed the ways university students access and interpret religious information. Social media platforms such as TikTok, Instagram, and YouTube have become primary spaces where students encounter diverse forms of religious content, ranging from educational dakwah to provocative narratives that may trigger tension and conflict. This phenomenon creates both opportunities and challenges for shaping religious moderation, particularly among first-semester students who are in the formative stage of constructing their intellectual and religious identities. This study aims to explore in depth the dynamics of religious moderation among first-semester students at IAINU Tuban within the context of digital polarization. A descriptive qualitative method was employed, utilizing semi-structured interviews, observations, and documentation as data collection techniques. Data were analyzed through thematic processes of reduction, presentation, and conclusion drawing. The findings reveal that students exhibit high social media engagement and are frequently exposed to short dakwah content circulated through algorithmic mechanisms. However, they also confront digital polarization characterized by emotional disputes, informational bias, and negative perceptions of other religious groups. While students demonstrate an initial understanding of religious moderation—such as wisdom, tolerance, and resistance to provocation—they have not fully developed adequate religious digital literacy to critically evaluate extreme content. This research concludes that social media simultaneously serves as a medium for dakwah and a site of polarization, highlighting the need for systematic reinforcement of digital literacy and religious moderation within Islamic higher education.